Oxidizing Effect on Chemical Polymerization of Pyrrole Monomer in Anhydrous Media - Uzun, Sultan; Can, Muzaffer (Asian Journal of Chemistry, 2010)
The chemical polymerization of pyrrole monomer with ferric chloride (FeCl3), copper(II) perchlorate [Cu(ClO4)2], ammonium peroxodisulfate [(NH4)2S2O8] and periodic acid (H5IO6) in anhydrous medium was investigated by using conductivity measurements, thermal analysis methods (TG, DTA), UV-vis and FTIR spectroscopies. The results indicated that the best oxidation reagent for chemical polymerization of pyrrole in anhydrous medium was Cu(ClO4)2. It was also determined that FeCl3, which is both a Lewis acid and oxidant for chemical polymerization, adds to polymer chain such as proton.